Nonlinear characteristics of tuned liquid dampers - Yu, Jin Kyu, 1957- (My University, 1997)
In recent years, tuned liquid dampers (TLD) have been successfully employed in practice to mitigate undesirable structural vibrations. Although this device has many advantages, its damping mechanism has not been thoroughly investigated, nor are any definite guidelines available for TLD design. In this study, the behavior of TLD is investigated experimentally and numerically. The results are incorporated into the development of a design procedure.Shaking table experiments were conducted to investigate the characteristics of the shallow water sloshing motion in rectangular or circular tanks under small and large amplitude excitations. The results reveal that the most distinguishing characteristic of the shallow-water is a hardening-spring type nonlinearity. The nonlinearity is explicitly quantified using the jump-frequency as a function of excitation amplitude and tank size. It was found that the characteristics of nonlinearity are different in two regions: identified as the weak wave breaking and strong wave breaking regions.An equivalent TMD model was developed to capture the energy dissipation capacity of the TLD based on the experimental results by means of energy dissipation curve matching. The nonlinear stiffness and damping characteristics of the TLD were incorporated into this model as functions of excitation amplitude and tank size.A numerical fluid model using the random choice method to solve the shallow-water wave equations proposed by Gardarsson and Yeh (1994) was employed to simulate shallow-water sloshing motion in a rectangular tank. It was found that the model accurately simulated weak or moderate wave breaking. However, the model cannot capture the wave phenomenon under extremely strong excitation motions.Numerical schemes were developed to simulate the dynamic motions of a single-degree-of-freedom structure coupled with a TLD. Based on the captured nonlinear properties of the TLD, a nonlinear tuning procedure is proposed. The performance of TLDs in mitigating the structural vibration was evaluated using the interaction model of a structure with a proposed equivalent TMD. The results reveal that the nonlinear tuning enhances the TLD performance. A TLD design procedure under harmonic and white noise excitations is developed based on the results of performance investigations.Finally, the performance of TLDs under wind or earthquake conditions was investigated numerically. For the simulated wind condition, the selected TLD reduced the structural vibrations significantly. For the Northridge earthquake, the TLD was ineffective during the initial stage of the earthquake. The performance of the TLD for earthquake loadings must be further investigated.
Thesis (Ph. D.)--University of Washington, 1997
Keywords: Theses--Civil engineering